Prevalence of Abnormal Body Mass Index Among Students of a Private Sector Medical College in Pakistan (Medical Forum Monthly, 2024)
Objectives: To determine the status of BMI among the students of Frontier Medical College, Abbottabad and to find out the frequency of different BMI groups. Design of Study: Cross-sectional questionnaire based study. Place and Duration of Study: This study was conducted from 01.11.2010 till 10.03.2011 in Frontier Medical College, Abbottabad. Materials and Methods: A cross- sectional questionnaire based study was conducted in Frontier Medical College Abbottabad. Body weight and height of 400 students were measured and then their body mass index (BMI) was calculated. Keeping in view the WHO cut-offs, Under weight, Overweight and Obesity were defined. Results: 9.75 % of students fell in the underweight category. About 63.25 % were in normal range. 21 % were Overweight while no less than 6 % formed the various categories of obesity Conclusion: A significantly high proportion of students (36.75 %) were either over weight, obese or underweight. This is an alarmingly high percentage keeping in view the fact that all of them were 18-22 years of age. The students must be advised to take more care of their health status